Multi-ethnic computational thinking and cultural respect in unmanned aerial vehicle-assisted culturally responsive teaching - Lai, Ying-Hsun (Frontiers in Psychology, 2023)
As education systems worldwide begin to accept and implement computational thinking, the educators of both elementary and higher education are considering the cultivation of students’ computational thinking abilities. It is hoped that students effectively analyze and deconstruct all kinds of complex issues with computational thinking, and seek computer-executable ways to solve real-world problems. Through the integration of program education, students can learn and develop the abilities to practically apply their theoretical learning in information technology education. With the promotion of the concept of multicultural education, an increasing number of educational arenas are gradually introducing the concept of multicultural education to inculcate in students respect for different ethnic cultures via multicultural integration. In this study, unmanned aerial vehicle (UAV) technology was used to introduce culturally responsive teaching. The objective was to build a UAV-assisted culturally responsive teaching environment for multi-ethnic students that is based on their different thinking mechanisms formed by their respective cultures and living environments. Multi-ethnic students can attempt to solve problems employing computational thinking that is implemented when programing to control UAV. With the influence of culturally responsive teaching, the UAV-assisted learning strategies helped students and teachers of multi-ethnic groups understand different cultures and learn through mutual aid and cooperation. This study discussed the computational thinking abilities via different dimensions: logical thinking, programming ability, and cultural respect. The results showed that the introduction of UAV-assisted culturally responsive teaching method benefits not only indigenous students. For Han Chinese students as well, owing to the influence of cultural understanding, their overall learning effectiveness and cultural respect will be strengthened. Thus, this method improves the learning effectiveness in programming of multi-ethnic students, as well as of students with weaker prior programming ability. The method can also enhance the cognition and comprehension of different cultures in multicultural education.